Curcumin attenuates proangiogenic and proinflammatory factors in human eutopic endometrial stromal cells through the NF‐κB signaling pathway - Chowdhury, Indrajit; Banerjee, Saswati; Driss, Adel; Xu, Wei; Mehrabi, Sherifeh; Nezhat, Ceana; Sidell, Neil; Taylor, Robert N.; Thompson, Winston E. (Journal of cellular physiology, 2019)
Endometriosis is a chronic gynecological inflammatory disorder in which immune system dysregulation is thought to play a role in its initiation and progression. Due to altered sex steroid receptor concentrations and other signaling defects, eutopic endometriotic tissues have an attenuated response to progesterone. This progesterone‐resistance contributes to lesion survival, proliferation, pain, and infertility. The current agency‐approved hormonal therapies, including synthetic progestins, GnRH agonists, and danazol are often of limited efficacy and counterproductive to fertility and cause systemic side effects due to suppression of endogenous steroid hormone levels. In the current study, we examined the effects of curcumin (CUR, diferuloylmethane), which has long been used as an anti‐inflammatory folk medicine in Asian countries for this condition. The basal levels of proinflammatory and proangiogenic chemokines and cytokines expression were higher in primary cultures of stromal cells derived from eutopic endometrium of endometriosis (EESC) subjects compared with normal endometrial stromal cells (NESC). The treatment of EESC and NESC with CUR significantly and dose‐dependently reduced chemokine and cytokine secretion over the time course. Notably, CUR treatment significantly decreased phosphorylation of the IKKα/β, NF‐κB, STAT3, and JNK signaling pathways under these experimental conditions. Taken together, our findings suggest that CUR has therapeutic potential to abrogate aberrant activation of chemokines and cytokines, and IKKα/β, NF‐κB, STAT3, and JNK signaling pathways to reduce inflammation associated with endometriosis. Endometriosis is a chronic gynecological inflammatory disorder in which immune system dysregulation is thought to play a role in its initiation and progression. In the current study, we examined the effects of curcumin (CUR, diferuloylmethane ), an anti‐inflammatory folk medicine in Asian countries, on eutopic endometrial stromal cells derived from woman with or without endometriosis. The basal level of proinflammatory and proangiogenic chemokines and cytokines expression were higher in primary cultures of stromal cells derived from eutopic endometrium of endometriosis (EESC) subjects compared with normal endometrial stromal cells (NESC). The treatment of EESC and NESC with CUR significantly and dose‐dependently reduced chemokine and cytokine secretion over the time course. Notably, CUR treatment significantly decreased phosphorylation of the IKKα/β, NF‐κB, STAT3, and JNK signaling pathways under these experimental conditions. Taken together, our findings suggest that CUR has therapeutic potential to reduce inflammation associated with endometriosis.